Penerapan Metode Permainan Papan Memori untuk Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Sejarah Kelas X di SMK Arnoldus Betun - Maria I. Usu; Yuditha Sofiana Kofi; Yohanis Kristianus Tampani; Agusta De Jesus Mangalhaes (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This researcher aims to improve student learning activity in history subjects of class X SMK Arnoldus Betun through the application of the memory board game method. The formulation of the problem raised in this study is how to apply the memory board game method to improve student learning activity in history subjects and what is the impact of applying the memory board game method to improve student learning activity in history subjects. This researcher uses a classroom action research (CAR) method consisting of three cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The data collection instruments used are observation sheets and student learning interest questionnaires. The results of the study showed a significant increase in student learning interest after the application of the memory board game method. In the second cycle, the average student learning activity was at 60%, and increased gradually to reach 86% in the third cycle. The discussion of these results shows that the memory board game method is not only able to increase student learning activity, but also facilitates collaboration, active participation, and student creativity in the history learning process. Thus, it can be concluded that the memory board game method is effective in increasing the active learning of history among 10th-grade students at Arnoldus Betun Vocational School.